CASE-BASED REASONING PEMBERIAN REKOMENDASI PROFESI BERDASARKAN MINAT DAN BAKAT SISWA MENGGUNAKAN SIMPLE MATCHING COEFFICIENT SIMILARITY - Made Hanindia Prami Swari; Rahel Widya Arianti; Faisal Muttaqin (SINTECH (Science and Information Technology) Journal, 2020)
One of the applications of technology in psychology is a system for determination of interest and talent systems. The system of determining interests and talents in this case can be applied in determining professional recommendations based on the interests and talents of a high school student who will continue to lectures or jobs in accordance with their fields. A person's interests and talents can be known from habits, preferences and hobbies. The Case-based Reasoning system created in this study uses cases from respondents which is collected using a questionnaire containing some questions about a person's interest in. To match new cases with old cases stored on a case basis, the authors use the Simple Matching Coefficient similarity method. The system will recommend a suitable work after the user inputs his preferences and habits. based on the results of the tests conducted, it was found that the system had produced the same calculation between the values generated by the system and manual calculations. While based on testing that conducted on data test, it was found that the system was able to provide an accuracy value of 83.33%.